2018
DOI: 10.1016/j.joi.2018.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Google Scholar and Web of Science: Examining gender differences in citation coverage across five scientific disciplines

Abstract: Many studies demonstrate differences in the coverage of citing publications in Google Scholar (GS) and Web of Science (WoS). Here, we examine to what extent citation data from the two databases reflect the scholarly impact of women and men differently. Our conjecture is that WoS carries an indirect gender bias in its selection criteria for citation sources that GS avoids due to criteria that are more inclusive. Using a sample of 1, 250 U.S. researchers in Sociology, Political Science, Economics, Cardiology and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 37 publications
0
10
0
1
Order By: Relevance
“…For example, in the field of astronomy, papers authored by women received 10.4 ± 0.9% fewer citations than papers written by men [41]. The other suggests that there exists negligible gender difference in citations [42][43][44]. For example, there remains a marginal gender difference in citation impact among scholars in the field of management [45].…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, in the field of astronomy, papers authored by women received 10.4 ± 0.9% fewer citations than papers written by men [41]. The other suggests that there exists negligible gender difference in citations [42][43][44]. For example, there remains a marginal gender difference in citation impact among scholars in the field of management [45].…”
Section: Literature Reviewmentioning
confidence: 99%
“…1 It indicated that only 22% of the professionals in AI are women and that this low representation in a transformative field requires urgent action-otherwise, the AI gap has the potential to widen other gender gaps. Other studies have identified substantial gender gaps in science (Håkanson, 2005;Larivière et al, 2013;King et al, 2017;Andersen and Nielsen, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Most of these have found substantial gender disparities in favor of male researchers. They include work on journals of library and information science (Håkanson, 2005), on articles from the Web of Science (for Sociology, Political Science, Economics, Cardiology and Chemistry) (Ghiasi et al, 2016;Andersen and Nielsen, 2018), on articles from PubMed life science and biomedical research (Mishra et al, 2018), on articles from fifty disciplines published in JSTOR (King et al, 2017), and on publications from US research universities (Duch et al, 2012). There also exists some work that shows that in fields such as linguistics (LSA, 2017) and psychology (Willyard, 2011), the gender balance is either close to parity or tilted in favor of women.…”
Section: Introductionmentioning
confidence: 99%
“…4 Most studies on gender and authorship have found substantial gender disparities in favor of male researchers. They include work on ∼1700 articles from journals of library and information science (Håkanson, 2005), on ∼12 million articles from the Web of Science (for Sociology, Political Science, Economics, Cardiology and Chemistry) (Ghiasi et al, 2016;Andersen and Nielsen, 2018), on ∼2 million mathematics articles (Mihaljević-Brandt et al, 2016), on ∼1.6 million articles from PubMed life science and biomedical research (Mishra et al, 2018), on ∼1.5 million articles from fifty disciplines published in JSTOR (King et al, 2017), and on ∼0.5 million publications from US research universities (Duch et al, 2012). There also exists some work that shows that in fields such as linguistics (LSA, 2017) and psychology (Willyard, 2011), female and male participation is either close to parity or tilted in favor of women.…”
Section: Introductionmentioning
confidence: 99%
“…It indicated that only 22% of the professionals in AI are women and that this low representation in a transformative field requires urgent action-otherwise, the AI gap has the potential to widen other gender gaps. Other studies have identified substantial gender gaps in science (Håkanson, 2005;Larivière et al, 2013;King et al, 2017;Andersen and Nielsen, 2018). Perez (2019) discusses, through numerous examples, how there is a considerable lack of disaggregated data for women and how that is directly leading to negative outcomes in all spheres of their lives, including health, income, safety, and the degree to which they succeed in their endeavors.…”
Section: Introductionmentioning
confidence: 99%